Traditional knowledge and quantitative assessment of ethnomedicinal uses of plants in Lahaul valley of Himachal Pradesh - Sharma, Renu; Bharti, Aradhna; Kumar, Ashsish; Uniyal, Sanjay (Ethnobotany Research and Applications, 2025)
Background: Traditional knowledge (TK) on plants and their use forms the basis of local healthcare, especially in the high altitude regions of the Himalaya. Rapid transformation of these areas is threatening the rich TK with serious implications. The present study, therefore, focused on documenting the medicinal plant use amongst the tribal population of Lahaul, Himachal Pradesh. Methods: Field survey was conducted during summer (2022-2023) to document medicinal plant use among the Lahulas community. Five villages, namely Gondhla, Kardang, Khangsar, Tholang, and Yangla were surveyed based on their geographical location, accessibility, and cultural relevance. Information on uses of plant species was collected using semi-structured questionnaires (n=43) and participant observations, followed by quantitative analyses i.e., Fidelity Level (FL), Informant Consensus Factor (ICF), and Use Value (UV). Results: Forty-one plant species placed in 25 families were noted for treating 10 different categories of human ailments, with higher number of species being used to treat digestive problems (n=19). Leaves were most commonly used plant part (39%) followed by roots (21%). Quantitatively, the highest use value was recorded for Angelica glauca (UV=0.88), while Arnebia benthamii, Fragaria vesca, and Viola canescens showed 100% fidelity. The highest ICF was noted for respiratory problems (0.29). Conclusions: The study highlights the dependence of local communities on plants for medicinal purposes wherein a total of 41 plant species were used. The use of these species is guided by the rich TK. Therefore, documentation of TK is imperative for identifying future leads and also for knowledge preservation. Keywords: Ethnomedicine, Fidelity level, Informant consensus factor, Use value, Traditional knowledge